2015
DOI: 10.1088/0953-4075/48/23/234005
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for chiral discrimination using high harmonic generation in tailored laser fields

Abstract: Abstract. Chiral discrimination with high harmonic generation (cHHG method) has been introduced in the recent work by R. Cireasa et al (Nat. Phys. 11, 654 -658, 2015). In its original implementation, the cHHG method works by detecting high harmonic emission from randomly oriented ensemble of chiral molecules driven by elliptically polarized field, as a function of ellipticity. Here we discuss future perspectives in the development of this novel method, the ways of increasing chiral dichroism using tailored la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 39 publications
5
65
1
2
Order By: Relevance
“…Electron spin and orbital angular momentum can play an important role in well-established recollision-driven techniques such as photoelectron diffrac-tion and holography [35][36][37][38][39][40] or high harmonic generation [24,26,29,32,[41][42][43][44][45]. We have shown that the use of intense two-color counter-rotating bi-circular fields can drive electroncore recollision with a degree of spin polarization that depends on the recollision time and therefore on the recollision energy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electron spin and orbital angular momentum can play an important role in well-established recollision-driven techniques such as photoelectron diffrac-tion and holography [35][36][37][38][39][40] or high harmonic generation [24,26,29,32,[41][42][43][44][45]. We have shown that the use of intense two-color counter-rotating bi-circular fields can drive electroncore recollision with a degree of spin polarization that depends on the recollision time and therefore on the recollision energy.…”
Section: Discussionmentioning
confidence: 99%
“…The application of bi-circular fields can lead to the production of ultrashort circularly and elliptically polarized laser pulses in the XUV domain [25][26][27][28][29][30][31]. Their chiral nature offers unique possibilities for probing molecular chirality [32] or symmetry breaking [33] at their natural time scales via high harmonic generation spectroscopy. Recent theoretical work [13] has indicated that electrons produced upon strong field ionization with bi-circular fields are spin polarized.…”
Section: Introductionmentioning
confidence: 99%
“…The very latest, wide-ranging research discuss: the origin of homochirality in amino acids and sugars; 25 the control of chirality in crystalline growth; 26 the separation of charge using chiral molecules; 27 the detection of enantiomers in a mixture through highharmonic generation, 28,29 and chiral scattering as the source of orbital angular momentum transfer between an acoustic beam and matter. 30 In this work, our novel mechanism for enantiomer separation is outlined and we can conclude that the additional complexities involved in a two-beam technique would not provide any advantages over a single beam set-up; the mechanism is higher-order than the one beam scenario and, thus, produces weaker effects and a differential chiral force that is three orders of magnitude smaller than the single beam case.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main or implicit motivations for several of the recent studies in this area is the prospect of achieving, by optical means, a separation of particles-especially chiral molecules-of opposite handedness [7,10,43,[98][99][100][101][102][103][104][105][106][107][108][133][134][135][136][137][138][139][140][141][142][143][144][145]. Certainly such a capacity might have important commercial applications-notably in the pharmaceutical industry, where oppositely handed compounds can deliver drastically different effects.…”
Section: Relevance To Enantiomer Separationmentioning
confidence: 99%